Imiquimod Targets Toxoplasmosis Through Modulating Host Toll-Like Receptor-MyD88 Signaling - Hamie, Maguy; Najm, Rania; Deleuze-Masquefa, Carine; Bonnet, Pierre Antoine; Dubremetz, Jean-François; El Sabban, Marwan; El Hajj, Hiba (Frontiers in Immunology, 2021)
Toxoplasma gondii is a prevalent parasite of medical and veterinary importance. Tachyzoïtes and bradyzoïtes are responsible for acute and chronic toxoplasmosis (AT and CT), respectively. In immunocompetent hosts, AT evolves into a persistent CT, which can reactivate in immunocompromised patients with dire consequences. Imiquimod is an efficient immunomodulatory drug against certain viral and parasitic infections. In vivo, treatment with Imiquimod, throughout AT, reduces the number of brain cysts while rendering the remaining cysts un-infectious. Post-establishment of CT, Imiquimod significantly reduces the number of brain cysts, leading to a delay or abortion of reactivation. At the molecular level, Imiquimod upregulates the expression of Toll-like receptors 7, 11 and 12, following interconversion from bradyzoïtes to tachyzoïtes. Consequently, MyD88 pathway is activated, resulting in the induction of the immune response to control reactivated Toxoplasma foci. This study positions Imiquimod as a potent drug against toxoplasmosis and elucidates its mechanism of action particularly against chronic toxoplasmosis, which is the most prevalent form of the disease.